PERILAKU SUBJEK DALAM BAHASA KEMAK KABUPATEN BELU NUSA TENGGARA TIMUR - Budiarta, I Wayan (LITERA, 2016)
This study aims to identify subject characteristics of the Kemak language in Belu Regency, East Nusa Tenggara. The subject characteristics are identified by testing the arguments predicted as a subject. The data were spoken and written data in the form of clauses or sentences collected through the field linguistic method, using direct elicitation supported by interviews. The selected informants were native speakers. The findings show that the subject in the Kemak language has the following characteristics. (1) The subject appears in the pre-verbal position in the canonical structure. (2) An adverb and a negation marker can be inserted between the subject as a pre-verbal argument and the predicate. (3) The subject can be relativized. (4) A floating quantifier can be inserted between subject and predicate. (5) The subject can be made reflexive. (6) Non-subject arguments (direct and indirect objects) can be raised to be a subject through the raising mechanism. (7) The subject can be focused through the presence of the focus marker te "˜that’ which appears directly after the subject. (8) The subject can be controlled.